Prinsip Pernikahan dalam Cedaw Perspektif Hukum Islam - Ainiyah, Qurrotul (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2018)
In this study, we reviewed the law contents of article 16 in CEDAW (The Convention on the Elimination of All Forms of Discrimination against Women) which regulates the same rights and obligations between men and women in marriage based on the principles of equality and equity. The article 16 contents then analyzed with Islamic marriage principles. This study concluded that Islam placed every human as servant of God. Both men (husbands) and women (wives) have proportional rights and obligations, not necessarily the same, because both have rights and obligations that are different from the kind but will have the same value in servitude to God as a logical consequence of